Injuries in Argentinian football: an epidemiological study of six professional clubs of second-division during the 2022 season - Baldjian, A. C.; Sampietro, M.; Gays, C.; Brusco, A.; Mohrenberger, H.; Gimenez, G.; Menayed, R.; Villalba, F.; Tondelli, E.; Clarsen, B. (The Physician and Sportsmedicine, 2025)
Objectives To describe thepattern of injuries in the second division of men`s professional football in Argentina.